(untitled) (Revista Cerrados, 2010)
Eles não usam black-tie: a forma como conteúdo histórico-ideológico. O presente artigo analisa comparativamente a peça Eles não usam black-tie, de Gianfrancesco Guarnieri (1958) e o filme homônimo (1981) com direção de Leon Hirszman. Demonstramos que há uma dicotomia no texto de Guarnieri que se equilibra na configuração da forma interna da peça teatral e, verificamos que, na transposição da linguagem teatral para a linguagem cinematográfica, e pelas opções da adaptação em momentos diversos de nossa história política, essa balança se desequilibra. Desta forma, percebemos como, a partir de nossa matéria estética, podemos compreender o nosso devir histórico. Palavras-chave: teatro; cinema; história; arte e política. Arena and the engagement in modern Brazilian theatre. The present article analyses comparatively the play Eles não usam black-tie, by Gianfrancesco Guarnieri (1958), and the homonym movie (1981) with the direction of Leon Hirszman. We demonstrated that there is a dichotomy in Guarnieri’s text that balances in the internal shape configuration of the theatrical play and we verify that in the transposition from the theatrical language to the cinematographic language, and by the adaptation options in several moments of our political history, this scale unbalances. In this way, we noticed how from our esthetic matter we can comprehend our historical obligation and that even with the same content, the works are different in their formal options, in other words, modifying the way of the presentation of the contents, we modify the content itself. Keywords: theater; cinema; history; arts and politics.